SUPPORT SYSTEM OF TECHNOLOGY ENHANCED LEARNING INAN EDUCATIONAL INSTITUTION - Daiva Abromaviciene; Margarita Tereseviciene; Justina Naujokaitiene (European Scientific Journal, ESJ, 2014)
The main elements of support system while promoting TEL in an educational institution are discussed in this paper. While integrating TEL in an educational institution it is necessary to ensure technological support and resources for bothteachers and learners, organizational support, pedagogical support for teachers, peer and information advice and guidance support for learners. If an appropriate support system is implemented, the use of technologies will lead to a more efficient, acceptable, better processed and effective learning. Research results in a VET organizationhave shown that teachers do not get sufficient technological support, while organizational support needs enhancement. Best evaluated was pedagogical support, but teachers still need support while using web conference tools, social networks, mobile tools, as these tools are rarely used in the teaching process.